(untitled) (Communications in Computational Physics, 2020)
It is important to have detailed knowledge of large scale spacecraft reentering atmospheric disintegration and main structures melting ablation for an accurate estimate of debris spread area. The direct simulation Monte Carlo (DSMC) method is performed to simulate aerothermodynamic characteristics of Tiangong-1 simplified configuration in rarefied transitional regime during its reentry process. The hybrid Cartesian and surface unstructured triangular meshes as well as adaptive refinement are employed to deal with these complex configuration flows. Internal energy excitations and chemical reactions are considered to compute aero heating precisely. A large number of computational difficulties are solved by the DSMC parallel algorithm based on MPI environment. Hypersonic nitrogen flow of Mach 15.6 about a 25/55 deg biconic model is chosen as test cases for validation. The calculated pressure and heating rate distributions have good agreement with the experimental data. Based on the DSMC results of Tiangong-1 shape, the structure stress of solar panels connecting model is analyzed with finite element method. The heat conduction and ablation computations are performed on thin shell structure of spacecraft with one-dimensional model. The height of solar panels broken away from the spacecraft main body is preliminary estimated. The melting ablation of two module structure vehicle is analyzed for different reentering altitudes.